Расширение функций педагога как основное условие модернизации образования - Гомонова, В.Г. (My University, 2016)
The actual value of the given article reflects the modern necessity of up-dating the system of Kazakhstani education on the basis of new teacher’s functions. The question under consideration in the article is to investigate the functions that appear to actual in the circumstances of the ever changing world, e.g. the functions connected with Life-Long Learning, Project developing and Management in Education. The observed functions are crucial for teachers’ identification with the demands of the modern society, to increase the efficiency of the lesson in general.
Keywords: a teacher of new era; modern system of education; teacher’s functions; professional activities of the teacher